Understanding and Measuring Corporate Digital Responsibility: A Systematic Literature Review and Guidelines for Future Metrics - Pirttilä, Tiitus (2025)
Companies are increasingly facing pressure from various stakeholders to act responsibly, including in digital contexts. Digitalization and its ongoing devel-opment continuously reshape distinct aspects of corporate responsibility. Cor-porate Digital Responsibility (CDR) seeks to address the emerging responsibil-ity issues arising from digitalization by conceptualizing them and integrating them into corporate responsibilities. However, only creating frameworks and integrating new responsibilities into organizations is not enough to ensure re-sponsibility actions. Practices, actions and their impacts also need to be evalu-ated and tracked. This thesis aims to explore the evolving metrics for digital responsibility and to analyze the scientific discourse surrounding it. The topic is approached through a descriptive literature review that conceptualizes digi-tal responsibility. In addition, this thesis includes a systematic literature review that compiles research related to measuring responsibility within the frame-works of CDR and Corporate Social Responsibility (CSR). The systematic litera-ture review consists of two parts, as the first literature search aims to examine and analyze existing CDR metrics. The second search focuses on more ad-vanced CSR measurement metrics in order to identify practices that can sup-port the development of CDR metrics. As a result, the thesis demonstrates that the scientific discourse on the topic needs to be more structured and find com-mon ground regarding the frameworks. Moreover, the study proposes several guidelines for developing CDR metrics, addressing both recommendations for advancement and the challenges currently present in existing measurement tools.